The mechanisms of hot salt stress corrosion cracking in titanium alloy Ti-6Al-2Sn-4Zr-6Mo. (15th April 2018) - Joseph, Sudha; Lindley, Trevor C.; Dye, David; Saunders, Edward A.
Graphical abstract: Highlights: Hot salt stress corrosion in titanium alloy Ti6246 is investigated. Alloying elements Al and Zr are involved in the corrosion reactions. Cl was observed at the alloy/oxide interface, and may lead to interface debonding. Na2 TiO3, Al2 O3, ZrO2, TiCl2 deposit as nanoprecipitates under the salt. Hydrides were detected by XRD & HRTEM, which may relate to hydrogen embrittlement. Abstract: Hot salt stress corrosion cracking in Ti 6246 alloy has been investigated to elucidate the chemical mechanisms that occur. Cracking was found to initiate beneath salt particles in the presence of oxidation. The observed transgranular fracture was suspected to be due to hydrogen charging; XRD and high-resolution transmission electron microscopy detected the presence of hydrides that were precipitated on cooling. SEM-EDS showed oxygen enrichment near salt particles, alongside chlorine and sodium. Aluminium and zirconium were also involved in the oxidation reactions. The role of intermediate corrosion products such as Na2 TiO3, Al2 O3, ZrO2, TiCl2 and TiH are discussed.